Palaeoenvironmental implications of the giant crocodylian Mourasuchus (Alligatoridae, Caimaninae) in the Yecua Formation (late Miocene) of Bolivia - Tineo, David (2014)
Outcrops of the Yecua Formation (late Miocene) are exposed for approximately 230 m along the La Angostura section of the Piraí River (50 km southwest of Santa Cruz de la Sierra). These reveal massive (argillic palaeosols) and laminated (quiet-water lacustrine and marsh settings) mudstones interbedded with thin sandstones containing microfossils, molluscs and vertebrate remains. Significantly, the succession hosts a giant crocodylian, Mourasuchus (Alligatoridae, Caimaninae), which is represented by both skull and postcranial fragments found in association with freshwater turtles and fishes. Mourasuchus was distributed widely from the middle Miocene of Colombia to upper Miocene of Venezuela, Brazil and Argentina, suggesting connections between major fluvial systems and an active mechanism for dispersal of South American freshwater vertebrates during the Miocene.